2018
DOI: 10.1002/jcb.27859
|View full text |Cite
|
Sign up to set email alerts
|

CTRP3 inhibits high glucose–induced human glomerular mesangial cell dysfunction

Abstract: C1q/tumour necrosis factor–related protein‐3 (CTRP3) is a member of CTRP family, and its blood level is reduced in human and rodent models of obesity and diabetes. However, the role of CTRP3 in diabetic nephropathy remains unclear. This study was designed to examine the effects of CTRP3 on cell proliferation and extracellular matrix (ECM) accumulation in human glomerular mesangial cells (MCs) in response to high glucose (HG), and explore the potential molecular mechanisms. Our results demonstrated that the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…reported a protective role for CTRP3 in high glucose-induced glomerular mesangial cell dysfunction that was suggested as a cellular model of diabetic nephropathy [20]. CTRP3 exert its protective role via inactivation of janus kinase 2/signal transducers and activators of transcription 3 (JAK2/STAT3) in high glucose-induced glomerular mesangial cell [20]. The association between CTRP3 and Cr as well as eGFR are in vivo evidence for association of CTRP3 with diabetic nephropathy that confirm previous study by Hu et.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…reported a protective role for CTRP3 in high glucose-induced glomerular mesangial cell dysfunction that was suggested as a cellular model of diabetic nephropathy [20]. CTRP3 exert its protective role via inactivation of janus kinase 2/signal transducers and activators of transcription 3 (JAK2/STAT3) in high glucose-induced glomerular mesangial cell [20]. The association between CTRP3 and Cr as well as eGFR are in vivo evidence for association of CTRP3 with diabetic nephropathy that confirm previous study by Hu et.…”
Section: Discussionmentioning
confidence: 99%
“…The association between CTRP3 and Cr as well as eGFR are in vivo evidence for association of CTRP3 with diabetic nephropathy that confirm previous study by Hu et. al [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C1q/tumor necrosis factor-related protein 3 (CTRP3), a novel adipokine, belongs to the highly conserved CTRP superfamily of adiponectin paralogs [ 17 , 18 ]. Previous studies have demonstrated that CTRP3 is an endogenous antagonist of lipopolysaccharide [ 19 ] and that aberrant CTRP3 expression is related to multiple types of human disorders, such as arthritis [ 20 ], sepsis [ 21 ] and myocardiac dysfunction [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glomerular mesangial cells (GMCs) are groups of cells that function as key regulators in the renal system, and over-proliferation of GMCs was also considered as an important reason for the incidence and development of TIF [3][4][5] . Nevertheless, at the current stage, the roles of GMCs in the pathogenesis of TIF as well as the possible mechanism has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%